OVERCOMING TRAUMATIC EXPERIENCE THROUGH SELF- DEFENSE MECHANISM IN THE NOVEL THE BROKEN RING: THIS MARRIAGE WILL FAIL ANYWAY BY CHACHA KIM - Pebriyana, Aurelia; Panggabean, Waladdin (Prologue: Journal on Language and Literature, 2026)
This research aims to analyze overcoming traumatic experiences through self-defense mechanisms in the novel ‘The Broken Ring: This Marriage Will Fail Anyway’ by Chacha Kim. The objectives of this research are: to find out the types of traumatic experiences in the novel ‘The Broken Ring: This Marriage Will Fail Anyway’ by Chacha Kim, and to analyze how to overcome traumatic experiences through self- defense mechanisms in the novel ‘The Broken Ring: This Marriage Will Fail Anyway’ by Chacha Kim. This research employs Freud’s psychoanalysis theory to find out the types of traumatic experiences and the forms of self-defense mechanisms used to overcome those traumatic experiences. The method uses in this research is descriptive qualitative. The researcher found three types of traumatic experiences: neurotic trauma, trauma of loss and separation, and sexual trauma. The findings reveal seven forms of defense mechanisms: rationalization, suppression, denial, repression, displacement, reaction formation, and avoidance with.